Cultural isolation is greater than genetic isolation across an avian hybrid zone. (7th November 2016) - Kenyon, H. L.; Alcaide, M.; Toews, D. P. L.; Irwin, D. E.
Abstract: Elucidating the relationship between genetic and cultural evolution is important in understanding speciation, as learned premating barriers might be involved in maintaining species differences. Here, we test this relationship by examining a widely recognized premating barrier, bird song, in a hybrid zone between black‐throated green ( Setophaga virens ) and Townsend's warblers ( S. townsendi ). We use song analysis, genomic techniques and playback experiments to characterize the cultural and genetic backgrounds of individuals in this region, expecting that if song is an important reproductive barrier between these species, there should be a strong relationship between song and genotype. We show that songs in the hybrid zone correspond to the distinctly different songs found in allopatry but that song and genotype are not tightly coupled in sympatry. Allopatric individuals responded only to local songs, indicating that individuals may have learned to respond to songs they commonly hear. We observed discordance between song and genotype clines; a narrower cline suggests that cultural selection on song is stronger than natural selection on genotype. These findings indicate that song is unlikely to play a role in reproductive isolation between these species, and we suggest that spatial variation in song may nonetheless be maintained by frequency‐dependent cultural selection. This decoupling of genes and culture may contribute to hybridization in this region.